2002
DOI: 10.1515/cclm.2002.196
|View full text |Cite
|
Sign up to set email alerts
|

Blood Concentrations of Selenium, Zinc, Iron, Copper and Calcium in Patients with Hepatocellular Carcinoma

Abstract: We used an atomic absorption spectrophotometric method to determine the concentration of selenium, zinc, iron, copper and calcium in the whole blood of patients with hepatocellular carcinoma. The results demonstrate that these patients have a lower concentration of selenium (0.18 +/- 0.02 microg/ml vs. 0.28 +/- 0.06 microg/ml) and zinc (11.2 +/- 2.75 microg/ml vs. 18.2 +/- 7.33 microg/ml) than healthy controls (p < 0.05). On the other hand, the hepatocellular carcinoma patients have higher mean concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…With the search strategy stated before, 9 relevant records were included in our meta-analysis and data were extracted (Figure 1) [11, 12, 16, 17, 1921, 23, 24]. Table 1 summarized the characteristics of the 9 enrolled studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the search strategy stated before, 9 relevant records were included in our meta-analysis and data were extracted (Figure 1) [11, 12, 16, 17, 1921, 23, 24]. Table 1 summarized the characteristics of the 9 enrolled studies.…”
Section: Resultsmentioning
confidence: 99%
“…The following articles affirm the relationship between Se concentration and HCC. A matched-case-control study revealed lower blood Se levels among HCC patients [11]. There is another report on the obvious correlation relationship between low Se level and HCC in Korean hepatoma patients [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 25% of the enzymes in the body need to be activated by metal ions to carry out their metabolic functions. [6] Bioelements e.g. Copper and zinc are involved in vital biochemical activities like different redox and free radical formation and in maintaining cellular proton homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no proven influence of specific nutrients on risk of HCC, micronutrients may play a role 3,76–81 . Selenium is an essential micronutrient required for selenium‐containing anti‐oxidant enzymes such as superoxide dismutase.…”
Section: Prevention Of Nonviral Liver Disease‐related Hccmentioning
confidence: 99%